Interaction between Pericytes and Endothelial Cells Leads to Formation of Tight Junction in Hyaloid Vessels - Jo, Dong Hyun (Korea Society for Molecular and Cellular Biology, 2013)
The hyaloid vessel is a transient vascular network that nourishes the lens and the primary vitreous in the early developmental periods. In hyaloid vessels devoid of the support of astrocytes, we demonstrate that tight junction proteins, zonula occludens-1 and occludin, are regularly expressed at the junction of endothelial cells. To figure out the factor influencing the formation of tight junctions in hyaloid vessels, we further progress to investigate the interactions between endothelial cells and pericytes, two representative constituent cells in hyaloid vessels. Interestingly, endothelial cells interact with pericytes in the early postnatal periods and the interaction between two cell types provokes the up-regulation of transforming growth factor β1. Further in vitro experiments demonstrate that transforming growth factor β1 induces the activation of Smad2 and Smad3 and the formation of tight junction proteins. Taken together, in hyaloid vessels, pericytes seem to regulate the formation of tight junctions by the interaction with endothelial cells even without the support of astrocytes. Additionally, we suggest that the hyaloid vessel is a valuable system that can be utilized for the investigation of cell-cell interaction in the formation of tight junctions in developing vasculatures.